Political trends and groups in Csanád county in the 1840s - Deák Ádám (Belvedere Meridionale Szeged, 2023)
In the context of the study of political trends and groups in the Hungarian reform era, it is necessary examining the political life in the counties. In the 1840s, the nobility in Csanád county became increasingly divided into parties. In my study, I will examine conflicts between the nobles of Csanád and how the formation of the Conservative Party and the Liberal Party affected the political situation in Csanád county. In the context of the Diets, the election of deputies and the drafting of instructions also caused exciting clashes between the nobles, which greatly shades the picture of political trends.
Keywords: Bölcsészettudományok; Történettudomány és régészet